Computer-Aided Conceptual Design Through TRIZ-based Manipulation of Topological Optimizations - Cascini, G.; Cugini, U.; Frillici, F. S.; Rotini, F. (Cranfield University Press, 2009)
In a recent project the authors proposed the adoption of Optimization Systems [1] as a bridging element between Computer-Aided Innovation (CAI) and PLM to identify geometrical contradictions [2], a particular case of the TRIZ physical contradiction [3]. A further development of the research has revealed that the solutions obtained from several topological optimizations can be considered as elementary customized modeling features for a specific design task. The topology overcoming the arising geometrical contradiction can be obtained through a manipulation of the density distributions constituting the conflicting pair. Already two strategies of density combination have been identified as capable to solve geometrical contradictions.
Organised by: Cranfield University
Keywords: Computer-Aided Innovation; Computer-Aided Conceptual Design; Embodiment Design; TRIZ